Removal Study of Hazardous Thiols Pollution by Tributylammonium Halochromates (VI) / Silica, (C4 H9) 3 NH + [CrO3 X]- , (X=F, Cl): as an Oxidizing Agent - OICC Press Authors; Mohammad Kazem Mohammadi (Anthropogenic Pollution)
Oxidative coupling of thiols to the corresponding symmetrical disulfides were performed in the presence of silica gel supported tributylammonium fluorochromate(VI), (TriBAFC), and tributylammonium chlorochromate(VI), (TriBACC). Silica gel supported TriBAFC and TriBACC are versatile reagents for the effective and selective oxidation of organic substrates, in particular of thiol, under mild conditions. Disulfides are also key intermediates in a wide variety of organic synthetic routes. Considerable improvements are observed in the presence of the absorbent and making the work-up much more convenient. The nature of the solvent does not appear to be particularly critical. Hydrocarbons, benzene, ethers and chlorinated hydrocarbons are equally effective, the practical choice being oriented by the solubility of the products and the desired reaction temperature. The IR spectra of TriBAFC and TriBACC are similar to that of other fluoro and chlorochromates, TriBAFC and TriBACC are soluble in water, dimethylformamide, acetonitrile, acetone and dichloromethane; they are only sparingly soluble in benzene, carbon tetrachloride, chloroform and hexane.